2021
DOI: 10.1093/gerona/glab195
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Is Associated With Poor Cognition: A Population-Based Study of 70-Year-Old Adults Without Dementia

Abstract: Background Individual conditions of metabolic syndrome (MetS) have been related to dementia, however, their combined impact on the preclinical stage is unknown. We investigated the associations between MetS and domain-specific cognitive function as well as the role of sociodemographic, cardiovascular, and genetic factors. Methods Within the Gothenburg H70 Birth Cohort Study-Birth cohort 1944, 1131 dementia-free participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Decreased heme biosynthesis in erythroid cells then causes anemia ( 30 ). Previous studies also showed that thiamine deficiency induced anorexia by inhibiting the hypothalamic adenosine monophosphate-activated protein kinase signal pathway and disrupting neuroendocrine feedback control of food intake and energy metabolism, which may be related to malnutrition in AD patients ( 31 ). Although adults with vitamin B12 or folate deficiency can also present with megaloblastic anemias, our results suggest that anemia in AD patients may be caused by TDP reduction more than folate or B12 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased heme biosynthesis in erythroid cells then causes anemia ( 30 ). Previous studies also showed that thiamine deficiency induced anorexia by inhibiting the hypothalamic adenosine monophosphate-activated protein kinase signal pathway and disrupting neuroendocrine feedback control of food intake and energy metabolism, which may be related to malnutrition in AD patients ( 31 ). Although adults with vitamin B12 or folate deficiency can also present with megaloblastic anemias, our results suggest that anemia in AD patients may be caused by TDP reduction more than folate or B12 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Most subjects finished their education at secondary level or even before that. Higher education can negatively influence the association between MetS and cognitive decline [ 7 ]. Similar to most studies concerning MetS, we also focus on the older population.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers link MetS with a dysfunction in global cognition and increased dementia risk [ 3 , 4 , 5 , 6 ]. Nevertheless, there is no agreement on the specific domains that are impaired [ 7 ]. Many studies demonstrated a strong association between MetS and lower frontal lobe functions, such as executive functions attention and verbal fluency [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations